Pakistan Rural Household Panel Survey 2012 (Round 1): Methodology and community characteristics - Nazli, Hina; Haider, Syed Hamza (International Food Policy Research Institute, 2012)
The Pakistan Strategy Support Program (PSSP) conducted this Rural Household Panel Survey (RHPS) during March-April 2012 in three provinces of Pakistan (Punjab, Sindh, and KPK). The survey aims to provide the quantitative basis to identify and address the urgent economic policy priorities related to the implementation of the Planning Commission’s Framework for Economic Growth.